(E)-2-[(2,4,6-Trimethoxybenzylidene)- amino]phenol - Kaewmanee, Narissara; Chantrapromma, Suchada; Boonnak, Nawong; Ching, Kheng Quah; Fun, Hoong Kun (International Union of Crystallography, 2014)
There are two independent molecules in the asymmetric unit of the title compound, C16H17NO4, with similar conformations but some differences in their bond angles. Each molecule adopts a trans configuration with respect to the methylidene C N bond and is twisted with a dihedral angle between the two substituted benzene rings of 80.52 (7) in one molecule and 83.53 (7) in the other. All methoxy groups are approximately coplanar with the attached benzene rings, with Cmethyl—O—C—C torsion angles ranging from 6.7 (2) to 5.07 (19). In the crystal, independent molecules are linked together by O—H N and O—H O hydrogen bonds and a – interaction [centroid–centroid distance of 3.6030 (9) A ° ], forming a dimer. The dimers are further linked by weak C— H O interactions and another – interaction [centroid– centroid distance of 3.9452 (9) A ° ] into layers lying parallel to the ab plane.